A high conductivity lithium manganese iron phosphate positive electrode material and preparation method thereof
By using glucose-coated carbon source, specific polymer additives and nanobubbler water-solvent thermal preparation technology in lithium manganese iron phosphate positive electrode materials, the problems of low conductivity and diffusion rate of the existing LiMPO4 positive electrode materials are solved, and the electrochemical performance and capacity retention rate of the material are significantly improved.
Patent Information
- Application Number
- CN202410886825.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-07-03
AI Technical Summary
The existing olivine-type LiMPO4 positive electrode materials have low electronic conductivity and lithium ion diffusion rates, which affects their application.
Glucose is used as the carbon coating source, polyvinyl difluoride with a small amount of 2,3-dimethoxyphenyl polymer mixed as a new additive, and nanofibbered water is used as a new reaction solvent, and a single-layer carbon-coated lithium manganese iron phosphate positive electrode material LiMn0.5Fe0.5PO4/C is prepared by solvent thermal method.
The conductivity and electrochemical properties of the material were improved, and the specific capacity for the first discharge at 0.1C reached 152.7mAh·g-1, and the capacity retention rate was still as high as 98.8% after 40 cycles.
Smart Images

Figure CN118658978B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and specifically refers to a high-conductivity lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] The high-quality development of electrochemical energy storage technology has an important driving force for my country. With the rapid development of electrochemical energy storage technology, it is particularly urgent to develop high-energy-density, low-cost, environmentally friendly, safe and stable lithium-ion battery positive electrode materials. At present, the positive electrode materials of lithium-ion batteries mainly include spinel structure materials (LiMn2O4), layered structure materials (LiCoO2, LiNiO2, LiNi 1-x-y Mn x Co y O2), olivine structure materials (LiFePO4, LiMnPO4) and other transition metal oxides and phosphate series materials.
[0003] Olivine-type LiMPO4 (M=Fe, Mn, etc.) positive electrode materials have attracted much attention due to their high safety, strong stability, long cycle life, and stable charge and discharge platform. At present, the LiFePO4 material that has been commercialized on a large scale is gradually unable to meet people's needs. LiMnPO4 materials with higher voltage platforms and energy densities are beginning to enter people's field of vision. However, the inherent disadvantages of olivine-type LiMPO4, such as low electronic conductivity and lithium ion diffusion rate, seriously affect the application of the material. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a high conductivity lithium iron manganese phosphate positive electrode material and a preparation method thereof. The present invention uses glucose as a coating carbon source, and for the first time uses polyvinylidene fluoride mixed with a small amount of 2,3-dimethoxyphenyl polymer as a new additive, and nano bubble water as a new reaction solvent, and adopts a solvothermal method with determined optimal process parameters to prepare a single-layer carbon-coated lithium iron manganese phosphate positive electrode material LiMn 0.5 Fe 0.5 PO4 / C is the high conductivity lithium manganese iron phosphate positive electrode material of the present invention.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes a method for preparing a high-conductivity lithium iron manganese phosphate positive electrode material, wherein the chemical formula of the high-conductivity lithium iron manganese phosphate positive electrode material is LiMn 0.5 Fe 0.5PO4 / C, which has a layer of carbon coating epitaxially grown; the additive in the synthesis process of the high-conductivity lithium manganese iron phosphate positive electrode material is polyvinylidene fluoride mixed with a small amount of 2,3-dimethoxyphenyl polymer, the reaction solvent is nano bubble water, and the elemental stoichiometric ratio of Mn and Fe is 0.5; the coated carbon source of the carbon coating is glucose.
[0006] Preferably, the method for preparing the high-conductivity lithium manganese iron phosphate positive electrode material specifically comprises the following steps:
[0007] S1. Prepare the raw materials required for synthesizing high conductivity lithium manganese iron phosphate positive electrode material;
[0008] S2, using an ultra-micron bubble generating device to prepare nano bubble water;
[0009] S3, using the nanobubble water in step S2 as the reaction solvent, preparing LiFe by solvothermal method 0.5 Mn 0.5 PO4 positive electrode material;
[0010] S4, the LiFe in step S3 0.5 Mn 0.5 The PO4 positive electrode material is prepared into a single-layer carbon-coated lithium iron manganese phosphate positive electrode slurry, which is dried in a spray dryer and sintered in a tubular sintering furnace, and then naturally cooled to room temperature to obtain a single-layer carbon-coated lithium iron manganese phosphate powder LiMn 0.5 Fe 0.5 PO4 / C is the high conductivity lithium manganese iron phosphate positive electrode material of the present invention.
[0011] Preferably, in step S1, the raw materials required for synthesizing the high-conductivity lithium manganese iron phosphate positive electrode material include ethylene glycol, lithium source LiOH, phosphorus source H3PO4, manganese source MnSO4·H2O, iron source FeSO4·7H2O, 2,3-dimethoxyphenyl polymer, polydifluoroethylene, polytetrafluoroethylene, deionized water, ethanol and glucose.
[0012] Preferably, in step S2, the ultra-micron bubble generating device uses Ar-H2 mixed gas as a gas source and uses deionized water to synthesize nano bubble water; the prepared nano bubble water has a bubble content of 90% and an average bubble particle size of 400 nm.
[0013] Preferably, in step S3, the following steps are specifically included:
[0014] S3.1, taking 160 mL of the nanobubble water in step S2 and uniformly mixing it with ethylene glycol in a volume ratio of 1:1 to obtain a reaction solvent;
[0015] S3.2, adding 0.18 mol of lithium source LiOH into the reaction solvent in step S3.1 and stirring vigorously until the mixture is uniform, to obtain a mixed liquid 1;
[0016] S3.3, add 0.06 mol of phosphorus source H3PO4 into the mixed liquid 1 in step S3.2 and stir vigorously until the mixture is uniform to obtain a white suspension;
[0017] S3.4, add 0.03 mol of manganese source MnSO4·H2O and 0.03 mol of iron source FeSO4·7H2O in sequence to the white suspension in step S3.3 and stir vigorously until uniformly dispersed to obtain mixed liquid 2;
[0018] S3.5, adding 6 g of polyvinylidene fluoride mixed with a small amount of 2,3-dimethoxyphenyl polymer to the mixed liquid 2 in step S3.4 and stirring vigorously for 3 h to obtain a mixed liquid 3;
[0019] S3.6, after the mixed liquid 3 in step S3.5 is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, it is placed in an oven at a temperature of 180°C for 18 hours, cooled to room temperature, centrifuged, washed alternately with deionized water and ethanol, and dried in an oven at 80°C to obtain LiFe 0.5 Mn 0.5 PO4 positive electrode material.
[0020] Preferably, in step S4, the following steps are specifically included:
[0021] S4.1, LiFe in step S3 0.5 Mn 0.5 PO4 positive electrode material and glucose were added into deionized water at a mass ratio of 10:3 and mixed evenly so that the solid content reached 50%, thereby obtaining a single-layer carbon-coated lithium manganese iron phosphate positive electrode slurry;
[0022] S4.2, pouring the single-layer carbon-coated lithium iron manganese phosphate positive electrode slurry in step S4.1 into a spray dryer for drying, then transferring the obtained dry powder to a tubular sintering furnace for sintering in a nitrogen atmosphere, and naturally cooling to room temperature to obtain a single-layer carbon-coated lithium iron manganese phosphate powder LiMn 0.5 Fe 0.5 PO4 / C is the high conductivity lithium manganese iron phosphate positive electrode material of the present invention.
[0023] Preferably, the air inlet temperature of the spray dryer is 300° C., the air outlet temperature is 150° C., the drying time is 2 hours, and the sintering temperature of the tubular sintering furnace is 720° C., and the sintering time is 5 hours.
[0024] The beneficial effects achieved by the present invention are as follows:
[0025] The present invention designs and invents a high-conductivity lithium manganese iron phosphate positive electrode material based on comprehensive regulation of four aspects: adjusting the stoichiometric ratio of chemical elements, preventing the dissolution of multivalent metal ions, reducing the occurrence of oxidation / agglomeration phenomena, and optimizing preparation process parameters.
[0026] Based on the principle that the difference in the elemental stoichiometric ratio of Fe and Mn in the lithium iron manganese phosphate positive electrode material will also make the material express different in terms of electrochemical performance, the present invention attempts for the first time to set the elemental stoichiometric ratio of Fe and Mn in the lithium iron manganese phosphate positive electrode material to 0.5. In the lithium iron manganese phosphate positive electrode material, the Fe element can improve the electrical conductivity of the material, and the Mn element can improve the charging and discharging platform of the material, increase the energy density of the material, and at the same time increase the unit cell volume of the material, expand the ion diffusion channel, improve the electrochemical reversibility of the material, and improve the electrochemical performance of the material at a high rate. However, when the content of Mn in the material is too high, factors such as the low electronic conductivity and ion diffusion rate of the LiMnPO4 material will cause the electrochemical performance of the material to drop sharply. After continuous attempts, the present invention has found that when the elemental stoichiometric ratio of Fe and Mn in the lithium iron manganese phosphate positive electrode material is 0.5, the best electrochemical performance will be exhibited.
[0027] Based on the Mn 2+ Based on the principle that MnO dissolves in the electrolyte, causing MnO to deposit on the negative electrode surface, resulting in battery polarization and capacity deterioration, the present invention adopts a new strategy to prevent the dissolution of multivalent metal ions for the first time, that is, adding a new additive (polyvinylidene fluoride mixed with a small amount of 2,3-dimethoxyphenyl polymer) during the synthesis of lithium manganese iron phosphate positive electrode materials. The dual effects of this new additive (i.e., by coordinating and capturing Mn 2+ The ions are trapped in the positive electrode and a passivation layer is formed on the negative electrode) which can increase the capacity retention rate of the lithium manganese iron phosphate positive electrode material by 16.7% even after 300 cycles.
[0028] Based on the preparation process of lithium manganese iron phosphate positive electrode material, Fe 2+ , Mn 2+ The use of Ar-H2 inevitably leads to oxidation of the material, and although traditional antioxidants as reducing acids can effectively avoid oxidation, they will introduce varying degrees of impurities into the system to a certain extent, thereby weakening the electrochemical performance. The present invention uses nanobubble water as a new reaction solvent in the process of synthesizing lithium iron manganese phosphate positive electrode materials for the first time. On the one hand, nanobubbles provide sufficient surface energy to reduce the occurrence of material agglomeration in the solvothermal method. On the other hand, Ar-H2 acts as an antioxidant in the preparation process, reducing the introduction of unnecessary impurities into the system, which can effectively improve the electrochemical performance of the material. In addition, the preparation and storage costs of nanobubble water are much lower than those of traditional antioxidants, so it is expected to be widely used in the preparation process of lithium iron manganese phosphate positive electrode materials.
[0029] Based on the principle that the ratio of the synthetic solvent, reaction temperature, reaction time and heat treatment temperature in the preparation process of lithium iron manganese phosphate positive electrode material will affect the performance of the material, the present invention adopts a solvothermal method to prepare lithium iron manganese phosphate positive electrode material. As one of the means to prepare lithium iron manganese phosphate positive electrode material, the solvothermal method can effectively control the particle morphology and size of the material, so that the material can have the expected structure, thereby better showing the performance of the material. After continuous attempts, the present invention finally determined the optimal preparation parameters: the ratio of nano bubble water to ethylene glycol in the reaction solvent is 1:1; the oven temperature is controlled at 180°C during the insulation process, and the time is controlled at 18h. The particle size distribution of the lithium iron manganese phosphate positive electrode material under this preparation parameter is uniform and fine.
[0030] The high-conductivity lithium iron manganese phosphate positive electrode material of the present invention has excellent conductivity through comprehensive regulation of four aspects: adjusting the stoichiometric ratio of chemical elements, preventing the dissolution of multivalent metal ions, reducing the occurrence of oxidation / agglomeration, and optimizing the preparation process parameters. The electrochemical performance is ultimately manifested in that the first discharge specific capacity at 0.1C is as high as 152.7 mAh·g-1. After 40 cycles, the 0.1C capacity retention rate is still as high as 98.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The process flow of synthesizing the high-conductivity lithium iron manganese phosphate positive electrode material by the solvothermal method in Example 1 of the present invention;
[0032] Figure 2 The first charging curves of the high-conductivity lithium iron manganese phosphate positive electrode materials of Example 1 and Comparative Example 1 of the present invention at 0.1C;
[0033] Figure 3 This is a relationship diagram between the maximum derivative and the number of cycles of the high-conductivity lithium iron manganese phosphate positive electrode materials of Example 1 and Comparative Example 2 of the present invention at a voltage of 2.6 V;
[0034] Figure 4 The first charging curves of the high-conductivity lithium iron manganese phosphate positive electrode materials of Example 1 and Comparative Example 3 of the present invention at 0.1C;
[0035] Figure 5 The SEM morphology images of the high-conductivity lithium iron manganese phosphate positive electrode materials of Example 1 and Comparative Example 4 of the present invention;
[0036] Figure 6 This is the rate performance curve of the high conductivity lithium manganese iron phosphate positive electrode material of Example 1 of the present invention.
[0037] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0040] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0041] Example 1: The chemical formula of the high conductivity lithium iron manganese phosphate positive electrode material of Example 1 of the present invention is LiMn 0.5 Fe 0.5 PO4 / C, which has a layer of carbon coating epitaxially grown; the additive in the synthesis process of the high-conductivity lithium manganese iron phosphate positive electrode material is polyvinylidene fluoride mixed with a small amount of 2,3-dimethoxyphenyl polymer, the reaction solvent is nano bubble water, and the elemental stoichiometric ratio of Mn and Fe is 0.5; the coated carbon source of the carbon coating is glucose, and the specific preparation steps are as follows:
[0042] S1. Prepare the raw materials required for synthesizing high conductivity lithium manganese iron phosphate positive electrode material: ethylene glycol, lithium source LiOH, phosphorus source H3PO4, manganese source MnSO4·H2O, iron source FeSO4·7H2O, 2,3-dimethoxyphenyl polymer, polydifluoroethylene, polytetrafluoroethylene, deionized water, ethanol and glucose.
[0043] S2. Using Ar-H2 mixed gas as a gas source, an ultra-micron bubble generator is used to prepare deionized water into nano bubble water with an average bubble particle size of 400nm and a bubble content of 90%.
[0044] S3, take 160mL of the nanobubble water in step S2 and mix it with ethylene glycol in a volume ratio of 1:1 to obtain a reaction solvent; add 0.18mol of lithium source LiOH to the reaction solvent and stir vigorously until it is evenly mixed to obtain a mixed liquid 1; add 0.06mol of phosphorus source H3PO4 to the mixed liquid 1 and stir vigorously until it is evenly mixed to obtain a white suspension; add 0.03mol of manganese source MnSO4·H2O and 0.03mol of iron source FeSO4·7H2O to the white suspension in sequence and stir vigorously until it is evenly dispersed to obtain a mixed liquid 2; add 6g of polyvinyl difluoride mixed with a small amount of 2,3-dimethoxyphenyl polymer to the mixed liquid 2 and stir vigorously for 3h to obtain a mixed liquid 3; transfer the mixed liquid 3 to a hydrothermal reactor with a polytetrafluoroethylene liner, place it in an oven at a temperature of 180°C for 18h, cool it to room temperature, centrifuge it, wash it with deionized water and ethanol alternately, and dry it in an oven at 80°C to obtain LiFe 0.5 Mn 0.5 PO4 positive electrode material.
[0045] S4, the LiFe in step S3 0.5 Mn 0.5 PO4 positive electrode material and glucose are added to deionized water in a mass ratio of 10:3 and mixed evenly so that the solid content reaches 50%, thereby obtaining a single-layer carbon-coated lithium iron manganese phosphate positive electrode slurry; the single-layer carbon-coated lithium iron manganese phosphate positive electrode slurry is poured into a spray dryer, the air inlet temperature is set to 300°C, the air outlet temperature is set to 150°C, and a drying treatment is performed for 2 hours. Subsequently, the obtained dry powder is transferred to a tubular sintering furnace, sintered for 5 hours in a nitrogen atmosphere at 720°C, and naturally cooled to room temperature to obtain a single-layer carbon-coated lithium iron manganese phosphate powder LiMn 0.5 Fe 0.5 PO4 / C is the high conductivity lithium manganese iron phosphate positive electrode material of Example 1 of the present invention.
[0046] Comparative Example 1: Comparative Example 1 of the present invention has four groups of high conductivity lithium manganese iron phosphate positive electrode materials, and the chemical formulas are LiMnPO4 / C, LiMn 0.8 Fe 0.2 PO4 / C, LiMn 0.2 Fe 0.8 PO4 / C and LiFePO4 / C, that is, except that the elemental stoichiometric ratio of Mn and Fe elements is different from that in Example 1, the other preparation steps are consistent with those in Example 1.
[0047] Comparative Example 2: In the preparation process of the high-conductivity lithium iron manganese phosphate positive electrode material of Comparative Example 2 of the present invention, except that the new additive in Example 1 is not added, the other preparation steps are consistent with Example 1.
[0048] Comparative Example 3: The reaction solvent (a mixture of deionized water and ethylene glycol in a volume ratio of 1:1) used in the preparation process of the high-conductivity lithium iron manganese phosphate positive electrode material in Comparative Example 3 of the present invention is different from the reaction solvent (a mixture of nanobubble water and ethylene glycol in a volume ratio of 1:1) used in Example 1, and the other preparation steps are consistent with Example 1.
[0049] Comparative Example 4: Comparative Example 4 of the present invention has 3 groups of high-conductivity lithium manganese iron phosphate positive electrode materials, and the oven insulation temperatures are set to 90°C, 110°C and 150°C, respectively, which is different from Example 1 (oven insulation temperature 180°C), and the other preparation steps are consistent with Example 1.
[0050] Experimental example
[0051] 1. The charge and discharge performance test of the high conductivity lithium manganese iron phosphate positive electrode material of Example 1 of the present invention and Comparative Example 1 and Comparative Example 3 was tested and analyzed using the BTS-5V10mA battery performance test system produced by Shenzhen Xinwei Electronics Co., Ltd. The test was carried out in a constant current charge / discharge mode, with a test voltage range of 2.0-4.6V and an ambient temperature of 25°C. The relationship between the charge and discharge current and the charge and discharge rate is:
[0052] I = mNC;
[0053] Where I is the charge and discharge current in A; m is the mass of the active material in g; N is the theoretical specific capacity of the positive electrode material in mAh g -1 ; C is the charge and discharge rate, the unit is C.
[0054] 2. The present invention plots the maximum derivative of the electrochemical data of the high-conductivity lithium manganese iron phosphate positive electrode material of Example 1 and Comparative Example 2 into a dQ / dV curve, so as to observe the self-dissolution of Mn ions as the number of cycles increases through the trend of the curve.
[0055] 3. The scanning electron microscope used for the morphology characterization of the high-conductivity lithium iron manganese phosphate positive electrode materials in Example 1 of the present invention and Comparative Example 4 is a Zeiss Sigma 300 with Gemini field emission scanning electron microscope produced by Zeiss of Germany.
[0056] Results Analysis
[0057] Figure 2 The first charge curves of the high conductivity lithium manganese iron phosphate positive electrode materials of Example 1 and Comparative Example 1 of the present invention at 0.1C can be observed that LiFePO4, LiFe 0.8 Mn 0.2 PO4、LiFe 0.5 Mn 0.5 PO4、LiFe 0.2 Mn 0.8The discharge specific capacities of PO4 and LiMnPO4 are 133.5 mAh g -1 、131.5mAh·g -1 、152.7mAh·g -1 、110.7mAh·g -1 and 55.2mAh·g -1 It can be seen that although the specific capacity of the material does not increase much with the increase of Mn content, the energy density of the material has been greatly improved because the addition of Mn increases the average charge and discharge voltage of the material. As the Mn element content continues to increase, poor electrochemical performance is exhibited. This is because the extremely poor ion diffusion rate and electronic conductivity of the dominant LiMnPO4 itself cause the electrochemical performance of the material to drop significantly. It can be seen that in the high-conductivity lithium manganese iron phosphate positive electrode material of Example 1 of the present invention, when the element stoichiometric ratio of Mn and Fe elements is 0.5, the best electrochemical performance can be achieved, thereby improving the conductivity.
[0058] Figure 3 The maximum derivative curves of the high conductivity lithium iron manganese phosphate positive electrode materials of Example 1 and Comparative Example 2 of the present invention at a voltage of 2.6V and the number of cycles are shown in Figure 1. It can be observed that the maximum derivative curves of the high conductivity lithium iron manganese phosphate positive electrode materials of Example 1 and Comparative Example 2 continuously decrease with the increase of the number of cycles. This phenomenon can be attributed to the degradation of the positive electrode materials, that is, the continuous dissolution of Mn ions in the electrolyte. It is worth mentioning that the decrease in Example 1 with the addition of the new additive is much lower than that in Comparative Example 2 without the addition of the new additive. This is because the new additive is mixed with a small amount of 2,3-dimethoxyphenyl polymer polyvinyl difluoride by coordinating and capturing Mn 2+ The ions are trapped in the positive electrode and a passivation layer is formed on the negative electrode, so that the dissolution rate of Mn ions in the high-conductivity lithium manganese iron phosphate positive electrode material of Example 1 is slowed down, the capacity retention rate is increased by 16.7%, and the conductivity is further improved.
[0059] Figure 4 The first charge curves of the high conductivity lithium manganese iron phosphate positive electrode materials of Example 1 and Comparative Example 3 at 0.1C show that the discharge specific capacity (152.7 mAh·g -1 ) is much higher than the discharge capacity (104.6 mAh·g -1 ), this is because the nanobubbles in the new reaction solvent provide sufficient surface energy to reduce the occurrence of material agglomeration in the solvothermal method. On the other hand, Ar-H2 plays the role of an antioxidant in the preparation process, reducing the introduction of unnecessary impurities into the system, thereby comprehensively improving the electrochemical properties of the material and further improving the conductivity.
[0060] Figure 5 The SEM morphology of the high-conductivity lithium iron manganese phosphate positive electrode materials of Example 1 and Comparative Example 4 of the present invention shows that the material prepared at 90°C in Comparative Example 4 was synthesized to a certain extent during the carbon coating process; the material prepared at 110°C in Comparative Example 4 showed a nanorod-like structure, indicating that the material crystals further grew and improved during the carbon coating process; the particles at 150°C in Comparative Example 4 grew, but the particle shape was irregular; the particles of the material prepared at 180°C in Example 1 were better dispersed, all of which were nanoparticles of 50-100nm. The uniformly dispersed nanoparticles can make the material fully contact with the electrolyte, thereby reducing the phenomenon of poor electrochemical performance caused by factors such as low electronic conductivity of the material or low lithium ion diffusion coefficient, that is, the nanoparticle size under the preparation process of Example 1 is optimal, thereby improving the conductivity.
[0061] Figure 6 The rate performance curve of the high conductivity lithium manganese iron phosphate positive electrode material of Example 1 of the present invention is shown in FIG. Figure 1 It can be observed that after comprehensive regulation, the electrochemical performance of the high-conductivity lithium manganese iron phosphate positive electrode material of Example 1 of the present invention is finally specifically manifested as a first discharge specific capacity of up to 152.7 mAh·g at 0.1C. -1 Even after 40 cycles, the 0.1C capacity retention rate is still as high as 98.8%, which has excellent electrochemical performance. This is entirely due to the excellent high conductivity.
[0062] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high conductivity lithium manganese iron phosphate positive electrode material, characterized in that: The chemical formula of the high conductivity lithium manganese iron phosphate positive electrode material is LiMn 0.5 Fe 0.5 PO4 / C, which has a carbon coating layer epitaxially grown; the additive in the synthesis process of the high-conductivity lithium manganese iron phosphate positive electrode material is polyvinylidene fluoride mixed with a small amount of 2,3-dimethoxyphenyl polymer, the reaction solvent is nano bubble water, and the elemental stoichiometric ratio of Mn and Fe is 0.5:0.5; the coating carbon source of the carbon coating is glucose; The specific preparation steps are as follows: S1. Prepare the raw materials required for synthesizing high conductivity lithium manganese iron phosphate positive electrode material; S2, preparing nano bubble water using an ultra-micron bubble generating device; S3, using the nanobubble water in step S2 as the reaction solvent, preparing LiFe by solvothermal method 0.5 Mn 0.5 PO4 positive electrode material; S4, the LiFe in step S3 0.5 Mn 0.5 The PO4 positive electrode material is prepared into a single-layer carbon-coated lithium iron manganese phosphate positive electrode slurry, which is dried in a spray dryer and sintered in a tubular sintering furnace, and then naturally cooled to room temperature to obtain a single-layer carbon-coated lithium iron manganese phosphate powder LiMn 0.5 Fe 0.5 PO4 / C, i.e. high conductivity lithium manganese iron phosphate positive electrode material; In step S3, the following steps are specifically included: S3.1, taking 160 mL of the nanobubble water in step S2 and mixing it with ethylene glycol in a volume ratio of 1:1 to obtain a reaction solvent; S3.2, adding 0.18 mol of lithium source LiOH into the reaction solvent in step S3.1 and stirring vigorously until the mixture is uniformly mixed to obtain a mixed liquid 1; S3.3, add 0.06 mol of phosphorus source H3PO4 to the mixed liquid 1 in step S3.2 and stir vigorously until the mixture is uniform to obtain a white suspension; S3.4, add 0.03 mol of manganese source MnSO4∙H2O and 0.03 mol of iron source FeSO4∙7H2O in sequence to the white suspension in step S3.3 and stir vigorously until uniformly dispersed to obtain mixed liquid 2; S3.5, adding 6 g of polyvinylidene fluoride mixed with a small amount of 2,3-dimethoxyphenyl polymer to the mixed liquid 2 in step S3.4 and stirring vigorously for 3 h to obtain a mixed liquid 3; S3.6, after the mixed liquid 3 in step S3.5 is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, it is placed in an oven at a temperature of 180°C for 18 h, cooled to room temperature, centrifuged, washed alternately with deionized water and ethanol, and dried in an oven at 80°C to obtain LiFe 0.5 Mn 0.5 PO4 positive electrode material.
2. The method for preparing a high conductivity lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step S1, the raw materials required for synthesizing the high-conductivity lithium manganese iron phosphate positive electrode material include ethylene glycol, lithium source LiOH, phosphorus source H3PO4, manganese source MnSO4∙H2O, iron source FeSO4∙7H2O, 2,3-dimethoxyphenyl polymer, polyvinyl difluoride, polytetrafluoroethylene, deionized water, ethanol and glucose.
3. The method for preparing the high conductivity lithium manganese iron phosphate positive electrode material according to claim 2, characterized in that: In step S2, the ultra-micron bubble generating device uses Ar-H2 mixed gas as a gas source and uses deionized water to synthesize nano bubble water; the prepared nano bubble water has a bubble content of 90% and an average bubble particle size of 400 nm.
4. The method for preparing a high conductivity lithium manganese iron phosphate positive electrode material according to claim 3, characterized in that: In step S4, the following steps are specifically included: S4.1, LiFe in step S3 0.5 Mn 0.5 PO4 positive electrode material and glucose were added to deionized water at a mass ratio of 10:3 and mixed evenly so that the solid content reached 35%, thereby obtaining a single-layer carbon-coated lithium manganese iron phosphate positive electrode slurry; S4.2, the single-layer carbon-coated lithium iron manganese phosphate positive electrode slurry in step S4.1 is introduced into a spray dryer for drying, and then the obtained dry powder is transferred to a tubular sintering furnace for sintering in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a single-layer carbon-coated lithium iron manganese phosphate powder LiMn 0.5 Fe 0.5 PO4 / C, that is, high conductivity lithium manganese iron phosphate positive electrode material.
5. The method for preparing the high conductivity lithium manganese iron phosphate positive electrode material according to claim 4, characterized in that: The air inlet temperature of the spray dryer is 300° C., the air outlet temperature is 150° C., the sintering temperature of the tubular sintering furnace is 720° C., and the sintering time is 5 h.
Citation Information
Patent Citations
Positive electrode material, preparation method thereof, positive plate and lithium ion battery
CN114976025A
Lithium manganese iron phosphate composite positive electrode material and preparation method thereof
CN117673327A